Formação do professor para educação ambiental em Angola: uma análise do currículo do curso de Ensino da Biologia do Instituto Superior de Ciências da Educação, ISCED-Cabinda da Universidade 11 de Novembro, Cabinda/ Angola - Paulo Maldonado Suzi Buanga (2014)
It is unquestionable the importance of environmental education (EE) in the educational process for the formation of students able to make informed decisions and participate in discussions in their community with regard to environmental issues. Given the problems experienced in our society, the treatment of environmental issues in higher education is one of the conditions that contribute to changes and transformations of the capitalist model, which encourages overconsumption and reinforces social inequalities. Why environmental education (EE) is considered one of the ways of coping with the current environmental crisis: should collaborate with the creation of a just and sustainable relationship between society and nature-society and society, from the individual and local ways in which this relation manifests itself to the more collective and global. Whereas the reflections on environmental problems and solutions thereof must consider the inherent relationship between the local and the global, interested in investigating how the curriculum of Teaching Biology includes these dimensions. This study involved a group of teachers and students from the School of Biology, the Institute of Education Sciences at the University of Novembro-Cabinda/Angola 11, aiming to identify teaching practices and understandings with respect to the size and location on global environmental issues. Through qualitative research the contents of reports, plans and other teaching materials as Curriculum Proposal and Notebooks Teacher were analyzed. The analysis performed indicates that teachers and students are more familiar with local issues. As for the global aspects, teachers and students recognize the importance of linking local and global in environmental education practices. However, teachers do not implement these relationships demonstrated in their practices and students reported not having contact with the articulation of these relationships during the course. Thus, the paper suggests the introduction of the subject in teacher training.